Comparison of xenogenic bone bioimplant and calcium phosphate granules on experimental femoral bone defect healing in rabbits - GH Mousavi; D Mohajeri; F Sadeghpour Golzar (Āsīb/shināsī-i Darmāngāhī-i Dāmpizishkī, 2012)
Rebuilding and renovation of lost bone whether because of physiologic or pathologic factors was one of the surgeons’ motivations from the past. Osteogenesis of decalcified bone induced by growth factors contained in it. This study is to assay probability effect of decalcified bone and calcium phosphate granules on osteogenesis which is made in experimental flaw and it is as a laboratory pattern in rabbit femur.This experimental study is made on 15 male rabbits. Animals were divided randomly into 3 groups (control and treatments).After induction of general anesthesia, 2 holes in size of 2 mm in diameter was made using a dental bit in femur width to medullary channel. After surgery, the control group left untreated and decalcified bones was placed in group 2 and calcium phosphate granules were placed in group 3. Histopathological and histomorphometrical studies for evaluation of bone healing were carried out in experimental rats, which were euthanized after 45 days of the experiment using hematoxylin-eosin (H&E) staining method.In control group, defect seemed to be filled with woven bone and bone marrow spaces and in spite of a poor osteogenic activity. In calcium phosphate group, young bone trabeculas increased in number and bone trabeculas more organized. Histomorphometric results, observed that calcium phosphate granules has significant effect on bone healing than decalcified and control groups.